(untitled) (Global Journal of Human-Social Science, 2016)
This study examines the influence of Television programmes on youth dressing pattern in Taraba State University Jalingo The researcher employed Taro Yame s formula to select 100 students which formed the sample frame The study made use of focus group and quantitative survey for its methodology 8 participants formed the focus group while 100 selected students were distributed questionnaires All the questionnaires distributed were duly filled and retrieved by the researcher Data gathered for the quantitative survey were coded in SPSS version 22 and presented in tables with frequency counts and simple percentages while the focus group was textually analyzed The study revealed among other things that entertainment musical programmes are the most preferred and watched programmes by youths The study also revealed that youths imitate the hip hop hippies and makeup hairstyles shown on television programmes than any other form of dressing and imitating such dressing makes them appear indecent The study recommends that Universities and other tertiary institutions should take the issue of dress code serious punishing students who are found wanting Local Television presenters should dress decently at all times and no matter their kind of programmes they should know that they are role models and whatever they do is easily copied by the young ones